Peningkatan Pengetahuan Lansia Anggrek Bulan Untuk Pencegahan Kehilangan Gigi - Octarina; Cindy; Nugroho, Didi; Kusnoto, Joko; Roro Asyurati Asia, Raden; Sundjoyo, Mikha (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Dental and oral health for elderly is crucial and has impact on the individual’s general health. Physical decline in the elderly is characterized by skin starting to shrink, hair beginning to change colour, loss of bone density, ability to see up to loss of mucous teeth. Tooth loss can interfere with the function of chewing, speaking and aesthetics. This condition can be aggravated by poor dental and oral hygiene. Therefore, dental health education is important to provide elderly an information about how to maintain oral health and prevent dental problem. The method used in this research is by providing education through power point media, given to Anggrek Bulan Elderly Community in November 25th 2023. Evaluation of participants’ knowledge was carried out before and after education by giving assessment sheet in the form of multiple choices to determine the level of community knowledge. Based on evaluation results, it was found that there was an increase in knowledge among the participants. This can be seen in average value of post-test results which has increased.